Female X-linked Alport syndrome with somatic mosaicism - Yokota, Kana; Nozu, Kandai; Minamikawa, Shogo; Yamamura, Tomohiko; Nakanishi, Keita; Kaneda, Hisashi; Hamada, Riku; Nozu, Yoshimi; Shono, Akemi; Ninchoji, Takeshi; Morisada, Naoya; Ishimori, Shingo; et al. (Clinical and experimental nephrology, 2017)
Background X-linked Alport syndrome (XLAS) is a progressive, hereditary nephropathy. Although males with XLAS usually develop end-stage renal disease before 30 years of age, some men show a milder phenotype and possess somatic mosaic variants of the type IV collagen α5 gene ( COL4A5 ), with severity depending on variant frequencies. In females, somatic mosaic variants are rarely reported in XLAS, and it is not clear what determines severity. Methods Two females with somatic mosaic mutations in COL4A5 with variant frequencies of 17.9 and 22.1% were detected using the next-generation sequencing. One patient only had hematuria. The other, however, had moderate proteinuria, which is a severe phenotype for a female XLAS patient of her age. The molecular mechanisms for the severe phenotype were investigated by examining variant frequencies in urinary sediment cells and X chromosome inactivation patterns, and by looking for modifier variants in podocyte-related genes using the next-generation sequencing. Results The severe phenotype patient had a variant frequency of 36.6% in urinary sediment cells, which is not markedly high, nor did she show skewed X chromosome inactivation. However, she did have the heterozygous variant in COL4A3 , which can affect severity. Conclusion Factors determining severity in female XLAS patients remain unclear. One studied patient with the somatic variant in COL4A5 showed a severe phenotype without skewed X chromosome inactivation, which might be derived from digenic variants in COL4A3 and COL4A5 . Further studies are required to determine molecular mechanisms behind female XLAS resulting in the severe phenotype.